Percepção dos cuidadores domiciliares de idosos sobre a atenção primária à saúde: autocuidado e assistência - MALCHER, Claudia Marques Santa Rosa (2022)
Introduction: Elderly caregivers represent a contingent of people who deal with the natural events of the aging process with the elderly, and who end up drawing attention for being a public of expressive number taking into account the population growth of the elderly and, as such, also , and equally, deserve investigation and attention from public policies for their relevant performance. In addition, an appropriate place of support for the monitoring of caregivers of the elderly is in Primary Health Care (PHC), as it is the main gateway to the SUS. Objective: This study aims to understand the perceptions and strategies of care and assistance that PHC offers to home caregivers of the elderly, from the point of view of subjective, social and home management implications. Methodology: 22 individuals were interviewed in a qualitative study that took place in the setting of a Family Health unit located in the capital of Maranhão, in São Luís, from November to December 2021. The content obtained from the interviews was analyzed by the methodology of Bardin. Result: Four categories were identified in this research: being a caregiver for the elderly; the need for caregiver support; coping with the caregiver in the face of the COVID-19 pandemic and designing the caregiver's future plans. Another point to highlight is that it was observed that caregivers do not recognize themselves as exercising this function and, although they exercise it, they consider themselves only as family members. It was possible to know the panorama of the reality of home care for the elderly in their needs and confrontations, where planning, support and balance in their activities and routine were identified as important in the realization of their future plans. Conclusion: it was found that there is a need to monitor the quality of life of caregivers of the elderly, as well as to monitor their assistance that is received by the health unit, especially in the pandemic. Improvements in PHC care for caregivers of the elderly should be encouraged for self-care.